Karl Polanyi - Isaac, Barry L. (Edward Elgar Publishing, 2005)
This unique Handbook contains substantial and invaluable summary discussions of work on economic processes and issues, and on the relationship between economic and non-economic areas of life. Furthermore it describes conceptual orientations that are important among economic anthropologists, and presents summaries of key issues in the anthropological study of economic life in different regions of the world. Its scope and accessibility make it useful both to those who are interested in a particular topic and to those who want to see the breadth and fruitfulness of an anthropological study of economics.
Anthropology
Keywords: economic anthropology; economics and finance; social policy and sociology

Polanyi and social economy - Isaac, Barry L. (A Handbook of Economic Anthropology, 2022)
Substantivism stemmed from the writings of Hungarian lawyer-turned-historian Karl Polanyi, who argued that capitalism is a historically unique kind of economy that is disembedded from the social matrix. By implication, the socially embedded pre-capitalist economies studied by anthropologists, historians and classicists cannot be understood using the formal economics developed to analyze capitalist economies. Rather, new tools for analysing their 'substantive' economies must be employed. Substantivism was championed in economic anthropology by economist-turned-anthropologist George Dalton and became the reigning paradigm in the subfield during the 1960s. Formalism arose in opposition, arguing that capitalist and pre-capitalist economies differ in degree, not in kind, and thus can all be analysed using the tools of microeconomics. Formalism largely displaced substantivism during the 1970s and 1980s as anthropologists increasingly focused on the economic integration of the world's peasant sectors into their national and regional economies.
Economics; Anthropology

A Handbook of Economic Anthropology, Second Edition: Orientations: Karl Polanyi - Isaac, Barry L. (A Handbook of Economic Anthropology, Second Edition, 2012)
Anthropology
Keywords: capitalist systems; economic anthropology; economic history; economic sociology; history of economic thought: individuals; political economy; social and economic stratification